Influence of ultrasonication time on solar light irradiated photocatalytic dye degradability and antibacterial activity of Pb doped ZnO nanocomposites. Issue 22 (15th November 2021) - Pavithra, M.; Jessie Raj, M.B.
Abstract: The current work reports, synthesis of co-precipitated 5 mol% lead doped zinc oxide nanocomposites by varying ultrasonication period as 7200 s, 14400 s and 21600 s hexagonal wurtzite structured, well defined (101) characteristic X-ray diffraction patterns of Pb/ZnO indicate that doping of lead and ultrasonication periods significantly altered the crystallite size. FTIR vibration band in the range of 450–600 cm − 1 confirms the formation of Pb/ZnO bond in nanocomposites. The optical band energy was calculated using Tauc's equation; it reveals that band energy is decreased with increase of sonication time. Dynamic light scattering study and SEM analysis confirms the particle size reduction of nanoclusters due to increasing sonication period. The antibacterial activity of the Pb substituted ZnO nanoparticles exhibits inhibition zones against pseudomonas aeruginosa, Escherichia coli, E. faccilis, klebsiella and stephylococcus pathogens. The sunlight assisted photo catalytic performance of samples show degradability of methylene blue and reactive red 120 dyes present in aqueous media. As Pb/ZnO nanocomposites prevent bacterial contamination and have excellent dye removal ability, show its suitability of dye degradation applications in industry under direct sunlight.